Time-frequency analysis of the AE signals generated by PDs on bushing and stand-off insulators - T. Boczar; S. Borucki; A. Cichoń; M. Lorenc (Archives of Acoustics)
The subject matter of this paper refers to the application of the acoustic emission method (AE) for the measurement and analysis of the pulses (AE) generated by surface partial discharges (SPD) occurring on bushing and stand-off insulators. Within the research work carried out, the results of which are presented in this paper, the AE pulses generated by SPDs were measured at meteorological and technical parameter changes for high-voltage experiments carried out. The range of the research work included the comparison of the timefrequency analysis results of the AE pulses generated by SPDs in a bushing insulator at the distance changes between an insulation grip and a ferrule, and at the internal electrode diameter changes. In Summing-up the comparative analysis was carried out for the results obtained in the time-frequency domain for bushing and stand-off insulators.